Analytical study of Kala Sharir on the principles of histology - Gaurav Soni (Wolters Kluwer Medknow Publications, 2021)
Background: Susrutha Samhita is the earliest treasure of anatomical concepts which illustrates the structures on both gross and microscopic levels. Susrutha has systematically described the process of dissection. This process of dissection gave a glimpse of all the body structures to Susrutha; which he dictated in further chapters of Sharir Sthana (a subunit related, especially with the description of anatomy) and other places wherever required. Several concepts are so unique to Susrutha that he is quoted as it in further hierarchal compendiums. Kala Sharir is one of such topics which despite the fact is being a miniscule structure, is described with supreme authority with location, enumeration, examples, and clinical utility. The exact efficacy of Gyan Chaksu (intellectual visualization) and Upmana Pramana (comparative tools) can be seen in the description of Kala Sharir, which after centuries and series of discoveries of the microscope has got its place in now days world as a separate entity of epithelium/tissue/membrane in histology, a subunit of anatomy. Objective: The objective was to study and analyze the structural entity and utility of Kala Sharir, in the illumination of the knowledge of contemporary histology. Data Source: Kala related literature from classical texts such as Susrutha Samhita, Ashtanga Sangraha, Ashtanga Hridaya, Bhavprakasha, and Sharangdhar Samhita. Histological texts of contemporary anatomy, journals, articles, internet material, and previous research papers related to these subjects. Review Methods: All the literature related to Kala Sharir is reviewed by comparing and analyzing the different meanings and thoughts of classical as well as contemporary authors. A separate analysis of commentaries on classical texts is done for better understanding. Results and Conclusion: The concept of Kala Sharir has here been studied analytically in the radiance of histology to understand its utility in clinics and understanding in contemporary view.